Metallurgical process engineering - Yin, Ruiyu (Metallurgical Industry Press Springer, 2011)
"Metallurgical Process Engineering" discusses large-scale integrated theory on the level of manufacturing production processes, putting forward concepts for exploring non-equilibrium and irreversible complex system. It emphasizes the dynamic and orderly operation of the steel plant manufacturing process, the major elements of which are the flow, process network and program. The book aims at establishing a quasi-continuous and continuous process system for improving several techno-economic indices, minimizing dissipation and enhancing the market competitiveness and sustainability of steel plants. The book is intended for engineers, researchers and managers in the fields of metallurgical engineering, industrial design, and process engineering. Prof. Ruiyu Yin is honorary president of the Central Iron and Steel Research Institute, China, and a member of the Chinese Academy of Engineering.